Natural Tourism Park Development Strategy With The Concept Of Education, Recreation And Conservation Towards The Visiting Interest Of The Community Of Batam City - Fairuzzabadi, Fairuzzabadi; Sidabutar, Yuanita FD; Amelia, Cevy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Sekupang Deer Park is located on Jalan RE. Martadinata, Tanjung Pinggir Village, Sekupang District is a new tourist icon in Batam City. This tourist park, which carries the "Smart and Green Garden" concept, has an area of 12 hectares and is equipped with jogging track facilities, fountains, fish farming ponds, fishing ponds and children's playgrounds. Several types of animals found in the Sekupang Deer Park include deer, kate chickens, pigeons, koi fish, goldfish, tilapia and catfish. At Sekupang Deer Park, visitors can also learn plant cultivation techniques using a hydroponic system, how to make compost fertilizer, as well as a system for recycling water and electricity from solar power. With the various facilities available, Sekupang Deer Park is one of the choices of places to visit for the people of Batam City and tourists visiting Batam City. A natural tourist park is a natural conservation area which can also be used as a tourism location or recreation facility. Ecotourism is a tourism activity that is environmentally friendly by prioritizing aspects of nature conservation, aspects of socio-cultural economic empowerment of local communities as well as aspects of learning and education. This research aims to analyze the influence of developing a tourist park with the concepts of education, recreation and conservation on the interest in visiting the people of Batam City. The research method uses a quantitative approach with survey techniques using questionnaires distributed to respondents who are residents of Batam City. The collected data was analyzed using a simple linear regression method to determine the extent to which tourist park development variables influence the interest in visiting the people of Batam City. The results of the research show that the development of a tourist park with the concepts of education, recreation and conservation has a significant positive influence on the interest in visiting the people of Batam City. The existence of educational facilities, recreational activities and nature conservation efforts in tourist parks can increase public interest in visiting and participating in these activities.